Efficacy and safety of recombinant human granulocyte colony-stimulating factor in patients with unexplained recurrent pregnancy loss: a protocol for a multicenter, randomized, double-blind, controlled trial - Mu, Fangxiang; Cai, Zhuhua; Du, Lirong; Zeng, Xianghui; Zhou, Qi; Chen, Yaolong; Wang, Fang (Current controlled trials in cardiovascular medicine, 2025)
Unexplained recurrent pregnancy loss (uRPL), defined as the loss of two or more pregnancies without an identified cause, affects approximately 1-2% of women trying to conceive. Emerging evidence suggests that an imbalance in maternal-fetal immunological tolerance may play a key role in its pathogenesis. Granulocyte colony-stimulating factor (G-CSF), a glycosylated polypeptide chain cell growth factor, has shown promise in improving pregnancy outcomes in uRPL, although findings from previous clinical trials are inconsistent. High-quality, adequately powered studies are urgently needed to determine its clinical utility. This study aims to evaluate the efficacy and safety of G-CSF in Chinese women with uRPL, providing a more theoretical basis for clinical practice. A randomized, double-blind, placebo-controlled, multicenter clinical trial will enroll 528 eligible participants, assigned to test group (n = 264, G-CSF 150 μg, subcutaneously every other day) and control group (n = 264, placebo), starting after confirmation of early pregnancy and ending at 10 weeks + 0 days of gestation. All participants will also receive dydrogesterone and aspirin as supportive care. The primary endpoint is fetal survival to 24 weeks, and secondary endpoints are early pregnancy loss, clinically confirmed pregnancy, ongoing pregnancy, fetal survival to 28 weeks, ectopic pregnancy, preterm birth, stillbirth, and pregnancy complications (preeclampsia, gestational diabetes mellitus, HELLP syndrome, placental abruption). The trial will also explore subgroup effects based on research centers (4 centers), age, number of pregnancy losses, and body mass index. This trial aims to provide high-quality evidence on the efficacy and safety of G-CSF in the treatment of uRPL, particularly in the Chinese population where existing data are limited. The findings may support evidence-based recommendations and inform treatment decisions in a population where therapeutic options remain limited and controversial. ChiCTR2300077436. Prospectively registered on 2023-11-08.